Ultrasound-assisted biosynthesis of novel methotrexate-conjugates - Noro, Jennifer Martins (2018)
New methotrexate-acylglycerols and methotrexate-cyclodextrins (, and -CD) conjugates were obtained via esterification or transesterification reactions. All reactions were catalysed by esterases namely immobilized Lipase from Candida antarctica B and Lipase from Thermomyces lanuginosus. The use of ultrasound to assist the reactions revealed to be a key factor to obtain high conversion yields on both MTX conjugates. Transesterification reactions including long chain triacylglycerols were only successful when ultrasound was applied. In cyclodextrins esterification a higher number of MTX molecules was also linked to cyclodextrins when ultrasound was used. All the conjugates were characterized by MALDI-TOF and NMR spectroscopy.